2010
DOI: 10.1038/jhg.2010.31
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of two genomewide association studies on blood pressure and essential hypertension in the Korean population

Abstract: Essential hypertension causes high rates of morbidity and mortality, primarily due to its complications, and its development is regulated by genetic risk and environmental factors. However, until recent genomewide association studies (GWASs) were reported, the genetic factors were unknown. Two GWASs on systolic blood pressure (SBP), diastolic blood pressure (DBP) and hypertension in Caucasians-Global Blood Pressure Genetics (Global BPgen) and Cohorts for Heart and Aging Research in Genome Epidemiology (CHARGE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 26 publications
4
45
1
2
Order By: Relevance
“…Se han llevado a cabo numerosos estudios genéticos sobre estos sistemas; sin embargo, los resultados han sido incongruentes entre poblaciones, lo que evidencia la heterogeneidad de la hipertensión arterial en su etiología genética en las poblaciones continentales (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58).…”
unclassified
“…Se han llevado a cabo numerosos estudios genéticos sobre estos sistemas; sin embargo, los resultados han sido incongruentes entre poblaciones, lo que evidencia la heterogeneidad de la hipertensión arterial en su etiología genética en las poblaciones continentales (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58).…”
unclassified
“…However, none of the SNPs was replicated in the Korean population at the genomewide significance level in these analyses (Hong et al, 2009;2010a). Recently, Hong et al identified 10 SNPs associated with blood pressure and hypertension risk using the KARE data, composed of 8842 individuals, and replicated three SNPs-17249754 of the ATP2B1 gene, rs1378942 in the CSK gene, and rs12945290 in the ARSG gene-in the Health2 data on 7861 subjects (Hong et al, 2010b). …”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these findings provide the first functional evidence to our knowledge that Plekha7 modulates BP by mediating systemic vascular resistance in a hypertensive rat strain. Moreover, to our knowledge these are the first mechanistic data to support multiple GWAS that have nominated PLEKHA7 as a hypertension risk gene (5,6,8,21,22) but had yet to demonstrate causality.…”
Section: Discussionmentioning
confidence: 99%
“…A single-nucleotide polymorphism (SNP) (rs381815, minor allele frequency 0.26) in intron 1 of the pleckstrin homology domain containing family A member 7 (PLEKHA7) gene, was identified by five independent GWAS to be associated with elevated systolic blood pressure and hypertension in multiple populations (5,6,8,21,22). The associated locus contains only the PLEKHA7 gene (5); however, the genetic mechanism(s) underlying this locus have not yet been functionally characterized.…”
mentioning
confidence: 99%
See 1 more Smart Citation